Identifying biopsychosocial factors that impact decompressive laminectomy outcomes in veterans with lumbar spinal stenosis: a prospective cohort study. Issue 3 (March 2021) - Weiner, Debra K.; Holloway, Kathryn; Levin, Emily; Keyserling, Harold; Epstein, Franklin; Monaco, Edward; Sembrano, Jonathan; Brega, Kerry; Nortman, Samuel; Krein, Sarah L.; Gentili, Amilcare; Katz, Jeffrey N.; et al.
Abstract : Abstract: One in 3 patients with lumbar spinal stenosis undergoing decompressive laminectomy (DL) to alleviate neurogenic claudication do not experience substantial improvement. This prospective cohort study conducted in 193 Veterans aimed to identify key spinal and extraspinal factors that may contribute to a favorable DL outcome. Biopsychosocial factors evaluated pre-DL and 1 year post-DL were hip osteoarthritis, imaging-rated severity of spinal stenosis, scoliosis/kyphosis, leg length discrepancy, comorbidity, fibromyalgia, depression, anxiety, pain coping, social support, pain self-efficacy, sleep, opioid and nonopioid pain medications, smoking, and other substance use. The Brigham Spinal Stenosis (BSS) questionnaire was the main outcome. Brigham Spinal Stenosis scales (symptom severity, physical function [PF], and satisfaction [SAT]) were dichotomized as SAT < 2.42, symptom severity improvement ≥ 0.46, and PF improvement ≥ 0.42, and analyzed using logistic regression. Sixty-two percent improved in 2 of 3 BSS scales (ie, success). Baseline characteristics associated with an increased odds of success were—worse BSS PF (odds ratio [OR] 1.24 [1.08-1.42]), greater self-efficacy for PF (OR 1.30 [1.08-1.58]), lower self-efficacy for pain management (OR 0.80 [0.68-0.94]), less apparent leg length discrepancy (OR 0.71 [0.56-0.91]), greater self-reported alcohol problems (OR 1.53 [1.07-2.18]), greater treatment credibility (OR 1.31 [1.07-1.59]), and moderate or severe magnetic resonance imaging-identified central canal stenosis (OR 3.52 [1.06-11.6]) moderate, OR 5.76 [1.83-18.1] severe). Using opioids was associated with lower odds of significant functional improvement (OR 0.46 [0.23-0.93]). All P < 0.05. Key modifiable factors associated with DL success—self-efficacy, apparent leg length inequality, and opioids—require further investigation and evaluation of the impact of their treatment on DL outcomes. Abstract : Self-efficacy, opioid use, and leg length inequality emerged as potential intervention targets to improve 1-year decompressive laminectomy success rates in Veterans with lumbar spinal stenosis.